2014
DOI: 10.1016/j.ijid.2013.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic contribution of 18F-FDG-PET/CT in fever of unknown origin

Abstract: Further studies to confirm the high diagnostic yield of (18)F-FDG-PET/CT observed in the present study would lend support to the inclusion of this imaging modality in the initial diagnostic work-up of patients with suspected FUO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(28 citation statements)
references
References 27 publications
5
23
0
Order By: Relevance
“…The reported success rate and sensitivity of 18 F-FDG PET/CT in patients with FUO ranges between 33 and 75% and 72 and 100%, respectively [14,19,20,[23][24][25][26][27]. This is in line with our own findings of a success rate of 61% and a sensitivity of 77%.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The reported success rate and sensitivity of 18 F-FDG PET/CT in patients with FUO ranges between 33 and 75% and 72 and 100%, respectively [14,19,20,[23][24][25][26][27]. This is in line with our own findings of a success rate of 61% and a sensitivity of 77%.…”
Section: Discussionsupporting
confidence: 89%
“…Continuous data are presented as mean ( SD) and categorical data are presented as n (%). CT, computed tomography; ranging between 3 and 20% [23,25]. In the present study, 22% of the cases were attributed to neoplasia.…”
Section: Discussionsupporting
confidence: 42%
See 1 more Smart Citation
“…Unfortunately, these standard approaches generally exhibit a relative low sensitivity and specificity9). PET-CT has been used in some studies for the diagnosis and management of FUO, owing to its ability to assess the morphology and functional characteristics of the tissues simultaneously910). In Tokmak et al9)'s study reported that the estimated diagnostic accuracy, sensitivity and specificity of PET-CT for FUO were 90.5%, 93.8% and 80%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, no predictive model was validated. Three studies (28,34,46) reported how often scans altered diagnosis, and 2 studies (37,46) reported how often scans altered therapeutic decisions (Supplemental Table 10). For example, 18 F-FDG PET or PET/CT affected diagnostic and therapeutic management in 44% (46) and 36% of cases (37), respectively.…”
Section: Assessment Of Study Risk Of Bias and Applicabilitymentioning
confidence: 99%